One of potency of experienced of nature resources which can be exploited from be exploited from Bay Banten is fishery sector. According to annual report on duty fishery and oceanic of Regency Serang year 2001, production of fish of pelagic from territorial water of Bay Banten amount to 6.466,90 ton. Volume produce fish of small pelagic from Sub District Kesemen at 2001 equal to 1.325 ton or 20.49 % from totalizing the production fish of small pelagic in Regency Serang. As for fish of small pelag - M Prihatna Sobari; Wiwit Suswanti (Buletin Ekonomi Perikanan, 2007)
One of potency of experienced of nature resources which can be exploited from be exploited from Bay Banten is fishery sector. According to annual report on duty fishery and oceanic of Regency Serang year 2001, production of fish of pelagic from territorial water of Bay Banten amount to 6.466,90 ton. Volume produce fish of small pelagic from Sub District Kesemen at 2001 equal to 1.325 ton or 20.49 % from totalizing the production fish of small pelagic in Regency Serang. As for fish of small pelagic caught is domination by small fish ( Stolephorus spp), lemuru ( Sardinella longiceps), kembung ( Rastrelliger spp), cumi-cumi ( Loligo Spp) , tembang ( Sardinella fimbriata). This research study of mount prosperity of bagan motor fisherman in Regency Serang, pursuant to 11 indicators Bureau of Statistical Center ( BPS) in SUSENAS 1991. Result of this research indicate that mount prosperity of pursuant to 11 indicators of BPS, it shows that most of all the fisherman's households of bagan motor in Bay Banten. Regency Serang the included in category of high mount prosperity is 93.33% and category of meddle mount prosperity is 6.67%.